Toxicity and risk of induced second cancer for Hodgkin Lymphoma (HL) treatment using new modalities of radiotherapy for young patients - BoughaliaAssya- Benfetima Lyes- Saadi Samia- Bendjazia Djemaa -Boughrara Ouhid (University of Eloued جامعة الوادي, 2023)
During the last decade new modalities of radiotherapy were implemented in different radiation oncology department in Algeria. Most of them are based on the concept of inverse modulated radiotherapy (IMRT), volumetric modulated radiotherapy (VMAT) and or helical tomotherapy (HT). The purpose of this study is to explore the trade-offs between cancer care, toxicities of organ’s at risk and the risk of induced second cancer in case of hodgkin lymphoma. A cohort of 20 young patients treatment plans using Field-in-Field radiotherapy (3D-FIF) were assessed using mathematical model to predict the toxicity calculated by the normal tissue complication probability (NTCP) using Lyman-Kutcher-Burman model and the estimated absolute risk (EAR) for the organ’s at risk in case of Rt and Lt lung. The associated induced second cancer risk was computed using the organ equivalent dose (OED) defined as a mechanistic model in the A Bomb survivors and hodgkin’s patients data relevant to radiotherapy. The results showed that the mean dose received at right and left lung are (7.81±4.6) Gy and (8.74±3.8) Gy respectively. The calculated NTCP for pneumonitis lung end point were 4.2% and 4.5% which correspond to EUD mean = (5.98±3.16) and (6.21±3.49) Gy. The associated estimated absolute risk of induced second cancer was obtained for Right and left lung and are 4.39±3.24 and 5.54±3.41 per 10000 P-Y. Higher risk was observed for three patients of the studied cohort. EAR and toxicity modelling is a better way to evaluate Hodgkin’s lymphoma specially when it comes of young patients where the risk of induced second cancer is more important
Article
Keywords: TCP/NTCP; EAR; OED; Hodgkin Lymphoma; Cancer.